Three species of Amanita section Lepidella (Amanitaceae, Agaricales) from northern Thailand - Liu, Yuan S.; Kumla, Jaturong; Suwannarach, Nakarin; Sysouphanthong, Phongeun; Lumyong, Saisamorn (Phytotaxa, 2022)
The genus Amanita, comprising three subgenera and eleven sections, is one of the most species diverse genera within the class Agaricomycetes. To date, 54 species have been validly reported from Thailand. During surveys of macro-fungi in northern Thailand in 2019 and 2020, three Amanita species were collected and identified as the members of Amanita sect. Lepidella based on morphological and molecular data. Among the three species, two species were identified as A. aureofloccosa and A. manicata and A. aureofloccosa is reported as a new record in Thailand. Interestingly, the third species was distinct from all other known species within sect. Lepidella. We describe the third species as a new species, namely A. albicarnosa. All these three taxa are documented with morphological characteristics, a phylogenetic tree, line drawings, color photographs, and comparisons with morphologically similar taxa. A distributional map of the sampling sites and a key to the Thai species of Amanita sect. Lepidella are also provided.